2017
DOI: 10.7555/jbr.31.20160073
|View full text |Cite
|
Sign up to set email alerts
|

Host-guest interaction of β-cyclodextrin with isomeric ursolic acid and oleanolic acid: physicochemical characterization and molecular modeling study

Abstract: Ursolic acid (UA) and oleanolic acid (OA) are insoluble drugs. The objective of this study was to encapsulate them into β-cyclodextrin (β-CD) and compare the solubility and intermolecular force of β-CD with the two isomeric triterpenic acids. The host-guest interaction was explored in liquid and solid state by ultraviolet-visible absorption,1 H NMR, phase solubility analysis, and differential scanning calorimetry, X-ray powder diffractometry, and molecular modeling studies. Both experimental and theoretical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Cyclodextrins (CD) represent one of the complexing agents most commonly used in the pharmaceutical industry due to their ability to improve the physical, chemical, and biological properties of bioactive molecules, especially those extracted from plants [ 58 ], although there is controversy regarding side effects in the renal system, in which orally administered β-CDs have been shown to induce limited toxicity. Jiang et al (2017) and Gould and Scott (2005) [ 59 , 60 ] evaluated the inclusion of triterpene acids in β-CD and obtained favorable results regarding the fit and binding to the β-CD cavity [ 59 , 60 ]. Their data demonstrated that the molecular interaction and complex formation between these compounds is given by the increased number of hydrogen bonds and hydrophobic interactions that promote conformational adjustments to take maximum advantage of the weak van der Waals forces in the hydrophobic cyclodextrin cavity [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclodextrins (CD) represent one of the complexing agents most commonly used in the pharmaceutical industry due to their ability to improve the physical, chemical, and biological properties of bioactive molecules, especially those extracted from plants [ 58 ], although there is controversy regarding side effects in the renal system, in which orally administered β-CDs have been shown to induce limited toxicity. Jiang et al (2017) and Gould and Scott (2005) [ 59 , 60 ] evaluated the inclusion of triterpene acids in β-CD and obtained favorable results regarding the fit and binding to the β-CD cavity [ 59 , 60 ]. Their data demonstrated that the molecular interaction and complex formation between these compounds is given by the increased number of hydrogen bonds and hydrophobic interactions that promote conformational adjustments to take maximum advantage of the weak van der Waals forces in the hydrophobic cyclodextrin cavity [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…During complexation, guest molecules and CD molecules come into contact with each other to unite and form a complex [ 50 ]. In most cases, one guest molecule forms a complex with one CD molecule, resulting in a 1:1 type of CD complex ( Figure 4 b) [ 4 , 26 , 51 ].…”
Section: Cyclodextrin Inclusion Complexesmentioning
confidence: 99%
“…Therefore, water is almost necessary in the formation of complexes [ 50 ]. During the complexation process, negative values of free energy changes by the Gibbs equation have been shown for ursolic acid (UA) and oleanolic acid (OA) with βCD and γCD, respectively, indicating that complexation was a spontaneous process [ 24 , 26 ].…”
Section: Cyclodextrin Inclusion Complexesmentioning
confidence: 99%
See 2 more Smart Citations